The Integration of Law and Virtue: Obedience in Aquinas's Moral Theology - Brown, Benjamin J. (Irish theological quarterly, 2002)
The recent recovery of the Aristotelian/Thomistic notion of virtue is generally seen as the antithesis of a legalistic approach to morality. As a result, the importance and role of law tend to be ignored by virtue ethicists, while related concepts such as duty and obedience get little attention. The author seeks to demonstrate the central significance of law, and a certain primacy of the virtue of obedience, in Aquinas's understanding of a specifically Christian virtue ethics.